Pengembangan Media Ular Tangga Edukatif pada Pembelajaran Pendidikan Pancasila di Kelas IV SDN Panancangan 5 - Brilianti Ismaila; Tifani Maulidah; Deva Radia Saputri; Ana Nurhasanah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to develop educational Snakes and Ladders media to increase student participation and engagement in Pancasila Education learning for fourth-grade students at SDN Panancangan 5. This study uses the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The needs analysis shows that low student participation is caused by the use of monotonous and one-way learning media. The developed product was validated by material experts and media experts. The first material validation obtained 95.29% and increased to 98.82% after revision, while media validation increased significantly from 60% to 95.38% after design improvements. The average expert validation score reached 87.37%, categorized as "very feasible." Implementation consisted of a small group trial involving 12 students, which resulted in a practicality score of 84.05%, followed by actual teaching involving 40 students with a score of 85.5%. The overall practicality average was 84.775%, categorized as "very practical." These findings indicate that the educational Snakes and Ladders media is feasible and practical to use to increase student participation and involvement in Pancasila Education learning.